1966
DOI: 10.1002/jsfa.2740171103
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the free amino and other nitrogen compounds in stored beef muscle

Abstract: Changes in the levels of 21 amino compounds, ammonium-N and urea-N. during the storage of fresh beef at various temperatures have been investigated. The meats were also subjected to bacteriological analysis. Glutathione and glutamine were found to decrease in the meats during storage, while most other aniinoacids, notably glutamic acid and tryptophan, increased. The increase in glutamic acid appeared to be related to the microbial numbers in the meats. On the other hand, the increase in tryptophan seemed direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Even proteases from microorganisms were not completely excluded in these studies of FAA changes and our present study. Large increases in glutamic acid were sometimes caused by bacterial metabolism of glutamine (Gardner & Stewart 1966). These overriding effects during storage would be larger than the effects of growth rate or breed in the present study, and such effects could be one of the main reasons for the inconsistencies in FAA data between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Even proteases from microorganisms were not completely excluded in these studies of FAA changes and our present study. Large increases in glutamic acid were sometimes caused by bacterial metabolism of glutamine (Gardner & Stewart 1966). These overriding effects during storage would be larger than the effects of growth rate or breed in the present study, and such effects could be one of the main reasons for the inconsistencies in FAA data between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Van den Berg et al (1963) and Khan and vander Berg (1964) noted appreciable increases in NPN after 5 weeks at o° C, though changes up to 10 d were negligible. Increases in ninhydrin-positive extractives (mainly amino acids) were, however, detectable after 7 d. Gardner and Stewart (1966), storing beef at 4 0 , 9 0 and 15° C, concluded that most amino acids, particularly glutamic acid and tryptophan, increased. Their data, however, show a decrease in glutamic acid up to 7-7 d at 4 0 C, although several other amino acids showed appreciable increases up to this time, some with sharp decreases later, presumably as a result of bacterial utilisation.…”
Section: Discussionmentioning
confidence: 93%
“…Apart from nutritional aspect, free amino acid is very important non-volatile materials for meat taste and flavour (Gardner and Sterwart, 1966;Davey and Gilbert, 1966), free amino acids from heated meat improve meat flavour (Ockerman and Cresopo, 1982). Tseng et al (2005) classified free amino acid in food to umami (aspartic acid, glutamic acid), sweet (serine, glycine, threonine, alanine), bitter (valine, methionine, isoleucine, leucine, phenylalanine, histidine, arginine), and others (Glutamine, tyrosine, systine, lysine and proline).…”
Section: A-bmentioning
confidence: 99%